On the design and properties of scaffolds based on vertically aligned carbon nanotubes transferred onto electrospun poly (lactic acid) fibers. (5th August 2017) - Rodrigues, Bruno V.M.; Razzino, Claudia A.; de Carvalho Oliveira, Francilio; Marciano, Fernanda R.; Lobo, Anderson O.
Abstract: Herein, we propose the design of a nanoscaffold based on the hot-press transfer of vertically aligned multi-walled carbon nanotubes (VAMWCNT) onto matrices of electrospun poly (lactic acid) (PLA) fibers. To this end, we created a three-dimensional, bioactive and electrically conductive scaffold that combines the potential of PLA as a biomaterial with the physical-chemical and biological properties of VAMWCNT (PLA/VAMWCNT). Given the well-known hydrophobicity of carbon nanotubes, oxygen-plasma functionalization was applied to the scaffolds in order to attach oxygen-containing groups to their surfaces, with the plasma treatment also responsible for the exfoliation of the VAMWCNT's tips. After plasma-functionalization, electrochemical measurements showed that our scaffold presented an increased electroactive area (1.5-fold) with a k o value of 6.87 × 10 − 3  cm s − 1, confirming its applicability as an electrode. Furthermore, we have also demonstrated the feasibility of electrodepositing nanohydroxyapatite (nHAp) crystals onto this nanoarchitectured material, improving its biomimetic and bioactive features. Preliminary biological assays revealed the viability of primary human osteoblast cells cultivated onto the PLA/VAMWCNT-nHAp scaffolds. This investigation has shed light on a practical approach to produce 3D–scaffolds by transferring VAMWCNT onto electrospun polymeric matrices. These novel materials may represent promising alternatives for future tissue engineering applications and thus should be studied further. Graphical abstract: Highlights: Vertically-aligned CNT were transferred onto poly (lactic acid) electrospun fibers. This novel material became superhydrophilic after oxygen-plasma functionalization. Our scaffold can act as a 3D electrode due to the electrical properties of the CNT. After plasma treatment, our scaffold underwent nanohydroxyapatite electrodeposition. Initial studies showed the adhesion and growth of osteoblast cells on our material